Insulin Resistance - Arora, Sarika (IntechOpen, 2012)
This book has been made possible by the contributions of leading scientists and clinicians from upcoming and interdisciplinary fields of research concerning the molecular and clinical features of insulin resistance. Multiple metabolic disturbances associated with Insulin Resistance include inflammatory cytokines, adipokines, endothelial dysfunction, tissue-specific defects in insulin action and signaling, oxidative stress, ectopic lipid deposition, and disordered neuroregulation. This book aims to encourage scientists and physicians - working separately on various aspects of Insulin resistance and metabolic syndrome for early detection of the first signs indicating the onset of a metabolic misbalance in order to prevent the consecutive cascades which lead to metabolic syndrome, resulting in the so-called diseases of modern civilization - cancer, diabetes and hypertension.